2022
DOI: 10.1002/art.41976
|View full text |Cite
|
Sign up to set email alerts
|

Excess Serum Interleukin‐18 Distinguishes Patients With Pathogenic Mutations in PSTPIP1

Abstract: Objective Dominantly inherited PSTPIP1 mutations cause a spectrum of autoinflammatory manifestations epitomized by PAPA syndrome (pyogenic sterile arthritis, pyoderma gangrenosum, and acne (PAPA) syndrome.). The connections between PSTPIP1 and PAPA syndrome are poorly understood, although evidence suggests involvement of pyrin inflammasome activation. Interleukin‐18 (IL‐18) is an inflammasome‐activated cytokine associated with susceptibility to macrophage activation syndrome (MAS). This study was undertaken to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
1
19
0
2
Order By: Relevance
“…Although the first patients described with CDC42-associated autoinflammatory disease had a remarkable response to IL-1 blockade 38 , more recent reports have noted that treatment with high dose IL-1 inhibition may not be sufficient to completely resolve symptoms, especially in the face of infection-driven macrophage activation syndrome 39 . In contrast to other autoinflammatory diseases, patients described to date have elevations in IL-18, suggesting a role for either the pyrin 82 84 or NLRC4 inflammasome in CDC42-mediated disease. Even though fewer than 10 cases have been described to date, the severity of disease phenotypes highlights the importance of an accurate diagnosis, and the name neonatal-onset cytopenia with dyshaematopoiesis, autoinflammation, rash and haemophagocytic lymphohistiocytosis syndrome has been proposed for CDC42-associated autoinflammatory diseases 39 .…”
Section: Aetiology Of Autoinflammatory Diseasesmentioning
confidence: 79%
See 1 more Smart Citation
“…Although the first patients described with CDC42-associated autoinflammatory disease had a remarkable response to IL-1 blockade 38 , more recent reports have noted that treatment with high dose IL-1 inhibition may not be sufficient to completely resolve symptoms, especially in the face of infection-driven macrophage activation syndrome 39 . In contrast to other autoinflammatory diseases, patients described to date have elevations in IL-18, suggesting a role for either the pyrin 82 84 or NLRC4 inflammasome in CDC42-mediated disease. Even though fewer than 10 cases have been described to date, the severity of disease phenotypes highlights the importance of an accurate diagnosis, and the name neonatal-onset cytopenia with dyshaematopoiesis, autoinflammation, rash and haemophagocytic lymphohistiocytosis syndrome has been proposed for CDC42-associated autoinflammatory diseases 39 .…”
Section: Aetiology Of Autoinflammatory Diseasesmentioning
confidence: 79%
“…Even for DIRA, which may be the most obvious example of links between genetics, disease and pathogenesis, patient-to-patient variability in therapeutic response still exists 60 . Similarly, there is increasing recognition of a role for inflammasome-driven IL-18 in some diseases, such as PAPA syndrome 84 , which may explain a lack of uniform responses to IL-1 blockade. Despite the general success in treating autoinflammation, the targeting of such a key mediator of inflammation, as well as the injectable nature of these therapeutics, has resulted in a search for additional therapies.…”
Section: Treatment Of Autoinflammatory Diseasesmentioning
confidence: 99%
“…Although IL-18/IL-18BP has significantly dysregulated in the abovementioned MAS-associated diseases, the imbalance of IL-18/IL-18BP has also been noticed in other inflammatory diseases, including rheumatoid arthritis (RA), psoriasis, asthma, lupus erythematosus, multiple sclerosis, atherosclerosis, renal and liver injury, inflammatory bowel disease (IBD), Crohn’s disease (CD), organ transplant rejection together with Graft versus host disease (GvHD), and most recently in pyogenic sterile arthritis, pyoderma gangrenosum, and acne (PAPA) syndrome [ 15 , 37 , 86 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 ], where cytokine imbalance is a major feature of these autoimmune disorders. The refractory monogenic inflammatory disorder, PAPA, resulted from a dominant mutation with the proline-serine-threonine phosphatase interacting protein 1 (PSTPIP1) gene and is characterized by acne and skin ulceration.…”
Section: Il-18bp In Autoimmune Diseasesmentioning
confidence: 99%
“…In addition, the autoimmune neutrophilic destruction of joints and skin is the major clinical presentation of PAPA, but it was not associated with MAS [ 149 , 150 ]. Moreover, a recently published study found that IL-18 is elevated in the patient serum and this elevation was highly associated with the disease outcome, again with no MAS risk [ 148 ].…”
Section: Il-18bp In Autoimmune Diseasesmentioning
confidence: 99%
“…Through these interactions, PSTPIP1 regulates several cellular functions, including interleukin-1 β (IL-1 β ) release, cytoskeletal organization, cell migration, and T cell activation [ 3 ]. However, as many patients mimicking PAPA syndrome lack the genetic finding, high levels of serum IL-18 seem to differentiate those who carry genetically pathogenic mutations in the PSTPIP1 gene [ 4 ].…”
Section: Introductionmentioning
confidence: 99%